Donor-driven harmonised payment of allowances policy and NGOs' community engagement in Malawi. Issue 1 (2nd January 2020) - Ngwira, Chikosa; Mayhew, Susannah
ABSTRACT: NGOs are recognised as key players in international development, yet recent studies have highlighted the complex problem of per diem allowances in the sector. In Malawi, donors responded and developed harmonised guidelines on payment of allowances. This study explored NGOs' responses to these harmonised guidelines and provides new insights. The findings show that the case study NGO dealt with multiple stakeholders' expectations and demands. Donors demanded compliance, so the NGO took steps to comply with the guidelines while trying to manage other stakeholders' expectations. In effect, compliance limited the NGO's operations, damaged its working relations and significantly increased their programme costs.